An RGD-modified hollow silica@Au core/shell nanoplatform for tumor combination therapy. (15th October 2017) - Li, Xin; Xing, Lingxi; Hu, Yong; Xiong, Zhijuan; Wang, Ruizhi; Xu, Xiaoying; Du, Lianfang; Shen, Mingwu; Shi, Xiangyang
Graphical abstract: Abstract: The combination of chemotherapy and photothermal therapy (PTT) in multifunctional nanoplatforms to improve cancer therapeutic efficacy is of great significance while it still remains to be a challenging task. Herein, we report Au nanostar (NS)-coated hollow mesoporous silica nanocapsules (HMSs) with surface modified by arginine-glycine-aspartic acid (RGD) peptide as a drug delivery system to encapsulate doxorubicin (DOX) for targeted chemotherapy and PTT of tumors. Au NSs-coated HMSs core/shell nanocapsules (HMSs@Au NSs) synthesized previously were conjugated with RGD peptide via a spacer of polyethylene glycol (PEG). We show that the prepared HMSs@Au-PEG-RGD NSs are non-cytotxic in the given concentration range, and have a DOX encapsulation efficiency of 98.6 ± 0.7%. The designed HMSs@Au-PEG-RGD NSs/DOX system can release DOX in a pH/NIR laser dual-responsive manner. Importantly, the formed HMSs@Au-PEG-RGD NSs/DOX nanoplatform can specifically target cancer cells overexpressing αv β3 intergrin and exert combination chemotherapy and PTT efficacy to the cells in vitro and a xenografted tumor model in vivo . Our results suggest that the designed HMSs@Au-PEG-RGD NSs/DOX nanoplatform may be used for combination chemotherapy and PTT of tumors. Statement of Significance: We demonstrate a convenient approach to preparing a novel RGD-targeted drug delivery system of HMSs@Au-PEG-RGD NSs/DOX that possesses pH/NIR laser dual-responsive drug delivery performance for combinational chemotherapy and PTT of tumors. The developed Au NS-coated HMS capsules have both merits of HMS capsules that can be used for high payload drug loading and Au NSs that have NIR laser-induced photothermal conversion efficiency (70.8%) and can be used for PTT of tumors.